Solution of Five-dimensional Schrodinger equation for Kratzer’s potential and trigonometric tangent squared potential with asymptotic iteration method (AIM) - Agung Budi Prakoso; A Suparmi; C Cari (Universitas Sebelas Maret, 2017)
Non-relativistic bound-energy of diatomic molecules determined by non-central potentials in five dimensional solution using AIM. Potential in five dimensional space consist of Kratzer’s potential for radial part and Tangent squared potential for angular part. By varying nr, n1, n2, n3, dan n4 quantum number on CO, NO, dan I2 diatomic molecules affect bounding energy values. It knows from its numerical data.